2017
DOI: 10.3892/ol.2017.7150
|View full text |Cite
|
Sign up to set email alerts
|

Patuletin induces apoptosis of human breast cancer SK‑BR‑3 cell line via inhibiting fatty acid synthase gene expression and activity

Abstract: Abstract. Fatty acid synthase (FASN) is a key enzyme involved in fatty acid biosynthesis and serves an important role in breast cancer development. The aim of the present study was to investigate the effects of patuletin on the gene expression and activity of FASN in the human breast cancer SK-BR-3 cell line, and the apoptotic effects of patuletin to breast cancer cells. Quantitative reverse transcription polymerase chain reaction, western blotting and intracellular FASN activity assays were used to evaluate F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Eupatin showed marked inhibitory effects on neuroinflammation and tau phosphorylation, which supported the conclusion that it has significant antiinflammatory properties (Chou et al, 2020). A previous study demonstrated that patuletin was able to inhibit FASN and showed antiproliferative and pro-apoptotic activities against human breast cancer cells (Zhu et al, 2017). These studies support the hypothesis that artemisinin is important in mammary gland development through the synergistic effects of its bioactive compounds.…”
Section: Kyoto Encyclopedia Of Genes and Genomes Pathway Enrichment A...supporting
confidence: 74%
“…Eupatin showed marked inhibitory effects on neuroinflammation and tau phosphorylation, which supported the conclusion that it has significant antiinflammatory properties (Chou et al, 2020). A previous study demonstrated that patuletin was able to inhibit FASN and showed antiproliferative and pro-apoptotic activities against human breast cancer cells (Zhu et al, 2017). These studies support the hypothesis that artemisinin is important in mammary gland development through the synergistic effects of its bioactive compounds.…”
Section: Kyoto Encyclopedia Of Genes and Genomes Pathway Enrichment A...supporting
confidence: 74%
“…The extract was found to contain a dominant amount of patuletin, a known O-methylated flavonol. This flavonol was shown to possess anti-proliferative and pro-apoptotic effects in human breast cancer cell line SK-BR-3 [49]. Moreover, patuletin and quercetagetin inhibited proliferation with an apoptotic activity in several tumor cell lines [50].…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that inhibition of FASN inhibits malignant biological behavior of colorectal cancer cells by down-regulating mTOR signaling pathway and energy metabolism [20]. Another FASN inhibitor Patuletin can promote the apoptosis of human breast cancer cell line SK-BR315 [21].In addition, FASN expression increased in HCC therefore, its inhibition may be a promising target for the treatment of this malignant tumor [22].…”
Section: Discussionmentioning
confidence: 99%